2014
DOI: 10.3233/rnn-139004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychotropic drugs on brain plasticity in humans

Abstract: Although neurotransmitter-based hypotheses still prevail current thinking about the mechanism of action of psychotropic drugs, recent insight into the pathophysiology of psychiatric disorders has unveiled a range of new therapeutic actions of the drugs used to treat those disorders. Especially antidepressants seem to exert at least some of their effects via restoration of synaptic/neuronal plasticity. In addition, there is increasing evidence that several of the second-generation antipsychotics and some antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 155 publications
0
7
0
Order By: Relevance
“…BDNF is an important neurotrophin/growth factor. Generally, BDNF is closely related to synaptic plasticity, hippocampal function and learning (Kuipers and Bramham, 2006;Cekic et al, 2012;Paulzen et al, 2014). FNDC5 is identified primarily as a PGC-1␣-dependent myokine, which is cleaved and secreted from muscle during exercise and induces some major metabolic benefits of exercise (Bostroem et al, 2012).…”
Section: Quercetin Regulates Synaptic Plasticity Via the Pgc-1α/fndc5mentioning
confidence: 99%
“…BDNF is an important neurotrophin/growth factor. Generally, BDNF is closely related to synaptic plasticity, hippocampal function and learning (Kuipers and Bramham, 2006;Cekic et al, 2012;Paulzen et al, 2014). FNDC5 is identified primarily as a PGC-1␣-dependent myokine, which is cleaved and secreted from muscle during exercise and induces some major metabolic benefits of exercise (Bostroem et al, 2012).…”
Section: Quercetin Regulates Synaptic Plasticity Via the Pgc-1α/fndc5mentioning
confidence: 99%
“…ErbB and its ligand epidermal growth factor (EGF) are reported to participate in both glioma development and schizophrenia neuropathology (Berezowska and Schlegel, 2011 ; Sotoyama et al, 2011 ; Iwakura and Nawa, 2013 ; Brocard et al, 2015 ), so antipsychotic drug targeting the EGF/ErbBs signaling pathway can affect the tumorigenesis of glioma in persons with schizophrenia. Clozapine, an atypical antipsychotic drug that treated schizophrenia by blocking the EGF/ErbBs systems (Paulzen et al, 2014 ), has been reported to inhibit the U87MG human glioblastoma cells proliferation (Shin et al, 2006 ; Jeon et al, 2015 ). Many studies showed that chlorpromazine could inhibit the Akt/mTOR pathway and induce autophagic cell death in glioma cells (Shin et al, 2013 ), and inhibit the TMZ-resistant glioma cells growth and proliferation in orthotopic mouse brain tumor models (Oliva et al, 2017 ).…”
Section: The Similar Mechanisms Involved In Glioma Tumorigenesis and mentioning
confidence: 99%
“…The mechanisms of both pharmacotherapy and TMS in the treatment of psychiatric disorders are at least partially based on changes in neuroplasticity 16 . Although All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of both pharmacotherapy and TMS in the treatment of psychiatric disorders are at least partially based on changes in neuroplasticity 16 . Although antidepressants are known to be modulators of neurotransmitters such as serotonin, dopamine, and noradrenaline 17 , modulation of neurotransmitters is not sufficient to completely explain their mechanism of action.…”
Section: Introductionmentioning
confidence: 99%